A study of starch resources with high-amylose content from five Chinese mutant banana species - Li, Bo; Xie, Baoguo; Liu, Jin; Chen, Xiaoai; Zhang, Yanjun; Tan, Lehe; Wang, Yitong; Zhu, Libin; Zhu, Kexue; Huang, Chongxing (Frontiers in Nutrition, 2022)
Investigation on staple crop starch of new species has been becoming the research focus of scholars at present. Based on this, the physicochemical properties and microstructural characteristics of starches isolated from Chinese mutant Musa acuminata Colla acuminata and double balbisiana (MA), Musa double acuminata cv. Pisang Mas (MAM), Musa acuminata cv. Pisang Awak (MAA), and Musa Basjoo Siebold (MBS), and Musa double acuminata and balbisiana-Prata (MAP) were investigated. Results exhibited that all starches exhibited high content of amylose (34.04–42.59%). According to the particle size, they were divided into medium (MA, MAM) (14.54–17.71 μm) and large (MAA, MBS, MAP) (23.01–23.82 μm) group. The medium group with A-type crystallization showed higher peak viscosity (PV), final viscosity, gel fracturability and gel hardness. For large group with B-type crystallization, the compact particle morphology, higher degree of crystallinity, short range order, gelatinization enthalpy, pasting temperature, lower porosity, water absorption capacity (WAC) and oil absorption capacity were found. In addition, the medium group with higher PV and gel hardness could be used as food thickening or gelling agents. The large group with higher Rc, short-range order, lower porosity and WAC could be potential to become raw material for resistant starch. All results showed the amylose content, had significant effect on the microstructure and physicochemical properties of starch samples. Outcomes in this investigation might provide a basis of theoretical application for industrial food production.